2009
DOI: 10.1021/jp8109622
|View full text |Cite
|
Sign up to set email alerts
|

Magainin 2-Induced Pore Formation in the Lipid Membranes Depends on Its Concentration in the Membrane Interface

Abstract: Antimicrobial peptide magainin 2 forms pores in lipid membranes to induce leakage of internal contents of cells, which is a main cause of its bactericidal activity. However, the conditions and the mechanism of its pore formation remain unclear. In this report, to reveal the effect of the surface charge density of membranes on magainin 2-induced pore formation, we investigated the interaction of magainin 2 with giant unilamellar vesicles (GUVs) composed of a mixture of electrically neutral dioleoylphosphatidylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
208
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(221 citation statements)
references
References 30 publications
13
208
0
Order By: Relevance
“…rIAPP and magainin 2 maintain stable pores at equilibrium. Peptides were first equilibrated with 200 μM 1,2-dioleoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DOPG) liposomes (in monomer units) for 48 h. Anionic DOPG was chosen as a simple model that reflects the importance of electrostatic interactions for binding and activity by both peptides (23,24). Leakage kinetics was then assessed by adding DPX extraluminally.…”
Section: Resultsmentioning
confidence: 99%
“…rIAPP and magainin 2 maintain stable pores at equilibrium. Peptides were first equilibrated with 200 μM 1,2-dioleoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DOPG) liposomes (in monomer units) for 48 h. Anionic DOPG was chosen as a simple model that reflects the importance of electrostatic interactions for binding and activity by both peptides (23,24). Leakage kinetics was then assessed by adding DPX extraluminally.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, when comparing results obtained from GUVs and LUVs, special caution should be given to the different conditions assessed in both experiments, as for instance, the significantly lower lipid concentration in GUVs experiments. Later, the same authors showed that the percentage of leakage was directly associated with the amount of membrane-bound magainin 2, modulated by the molar fraction of the anionic lipid PG in the membrane [46]. The kinetic pathway of magainin 2-induced pore formation was investigated in a subsequent work [47] through encapsulation of dyes of different size (1.4-3.6 nm radii).…”
Section: Visualizing the Peptide-induced Leakagementioning
confidence: 99%
“…In To complete the present discussion, it should be mentioned that giant unilamellar lipid vesicles (GUVs) with a diameter of ∼3 µm or more have been employed instead of LUVs to study the activity of membrane-active peptides. 41,49 The advantage of using GUVs is that they are sufficiently large that fluxes of fluorescent molecules into or out of individual vesicles can be directly imaged, including fluxes of fluorescent molecules of different sizes. 50 …”
Section: Experimental Approach Of the Articlementioning
confidence: 99%